Best practices beyond conventional knowledge management in schools. - Chua, Pei Pei. (2008)
Argue the case of a positive relationship from knowledge acquisition to improve problem solving to new knowledge generation to innovation output of which the entire value chain is largely dependent on the absorptive capacity of schools.